2018
DOI: 10.1021/acs.jpcc.8b05416
|View full text |Cite
|
Sign up to set email alerts
|

Computational Screening of Metal–Organic Frameworks for Membrane-Based CO2/N2/H2O Separations: Best Materials for Flue Gas Separation

Abstract: It has become a significant challenge to select the best metal–organic frameworks (MOFs) for membrane-based gas separations because the number of synthesized MOFs is growing exceptionally fast. In this work, we used high-throughput computational screening to identify the top MOF membranes for flue gas separation. Grand canonical Monte Carlo and molecular dynamics simulations were performed to assess adsorption and diffusion properties of CO2 and N2 in 3806 different MOFs. Using these data, selectivities and pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
111
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(115 citation statements)
references
References 63 publications
2
111
1
1
Order By: Relevance
“…It is also important to note that all our results are for single‐component and binary mixture gas permeabilities of MOF‐based MMMs and we neglected the presence of H 2 O in the flue gas stream. In our recent computational work, we showed the presence of humidity can reduce both the CO 2 and N 2 permeabilities of pure MOF membranes. In an experimental study, decreases in CO 2 and N 2 permeabilities of pure PIM‐1 membrane were observed in the presence of water.…”
Section: Resultsmentioning
confidence: 92%
“…It is also important to note that all our results are for single‐component and binary mixture gas permeabilities of MOF‐based MMMs and we neglected the presence of H 2 O in the flue gas stream. In our recent computational work, we showed the presence of humidity can reduce both the CO 2 and N 2 permeabilities of pure MOF membranes. In an experimental study, decreases in CO 2 and N 2 permeabilities of pure PIM‐1 membrane were observed in the presence of water.…”
Section: Resultsmentioning
confidence: 92%
“…As the MOF synthetic toolkit expands, the realization of MOFs with targeted designs becomes increasingly facile . Moreover, owing to the regularity and crystallinity of MOF structures, computational studies have been successful, and recent high‐throughput screening studies have helped in effectively guiding experimentalists . In situ or post‐synthetic modification, structural and pendant ligands, primary and auxiliary metals and metal clusters, as well as pore sizes, shape, acidity, and hydrophobicity modifications can direct the uptake capacities, selectivity, sensitivity, and mobility of MOFs and MOF components .…”
Section: Introductionmentioning
confidence: 99%
“…[20,28] Moreover,o wing to the regularity and crystallinity of MOF structures,c omputational studies have been successful, and recent high-throughput screening studies have helped in effectively guiding experimentalists. [29][30][31][32][33] In situ or post-synthetic modification, structural and pendant ligands,p rimary and auxiliary metals and metal clusters,a s well as pore sizes,s hape,a cidity,a nd hydrophobicity modifications can direct the uptake capacities,selectivity,sensitivity,and mobility of MOFs and MOF components. [20,28] MOFs have greater surface areas and higher degrees of tunability than other porous materials,s uch as zeolites,e ssential for applications including selective catalysis and low density,high capacity gas storage.C ompared to porous polymers,M OF crystallinity,p eriodicity,a nd permanent porosity makes characterization by X-ray diffraction techniques more amenable.Finally,while covalent organic frameworks (COFs) are often lighter and have larger pore structures that are more stable than in MOF counterparts,M OFs boast more diverse synthetic conditions and the additional tunability provided by the metal structural building unit (SBU)c an permit facile incorporation of photochemical properties,c atalytic centers, and gas sorption sites.…”
Section: Introductionmentioning
confidence: 99%
“…However, high-throughput computational screening can accelerate the discovery of new, functional materials for rational synthesis through the circumvention of the expensive and time-demanding synthesis and testing process. [26][27][28] High-throughput computational design has shown great success in identifying new molecules [29][30][31] and materials [32][33][34][35][36][37] with enhanced properties and advanced functionality. For many applications, first-principles studies are essential to virtual screening, but the high computational cost of these methods makes the search of large parts of the chemical space cost-prohibitive.…”
Section: Introductionmentioning
confidence: 99%